«DEBOTTLENECKING» IN THE MANAGEMENT SYSTEMS - V. Souponitsky (Вестник университета, 2016)
In the article the problems of improvement of modern control systems (CS) are considered. Specific examples are analyzed «bottlenecks» of the CS and ways of «debottlenecking». For the system of local self-government (LSG) and measures the «debottlenecking» in the Russian program «Development of mechanisms for the formation and establishment of a network of working groups promoting and monitoring the activities of Executive bodies in the Russian Federation» preliminary implementation of a pilot project on the territory of Moscow and Sevastopol. Personnel optimization of the CS possible through targeted training of specialists-managers of the best graduates of the cadet corps, proposed the corresponding program. Also are considered problems of optimization of information support for the CS. Special attention is paid to the issues of privatization of power in the CS, as these processes determine the main effects of corruption in the CS.